ЖАҢА ҚЫТАЙ ӘДЕБИЕТІНІҢ ҮЗДІК ЖАЗУШЫСЫ МАУ ДҮН. - Сейдахмет, Э. (Journal of Oriental Studies, 2016)
В статье рассматривается творчество и биография выдющегося писателя новой китайскоq литературы Мао Дуня. The article deals with the creative activity and biography of Mao Dun an outstanding writer of modern Chinese literature.